Nanoformulation Strategies: Emerging Innovations in Drug Delivery Systems - Tejas Naik; Sachin Datkhile; Sayali Wagh; Saniya Pathan (International Journal of Toxins and Toxics, 2026)
Nanotechnology is significantly advancing the pharmaceutical industry by introducing nanosystems that improve drug delivery, therapeutic efficacy, and patient outcomes. Various nanosystems-such as liposomes, dendrimers, polymeric nanoparticles, solid lipid nanoparticles, carbon nanotubes, and metallic nanoparticles-offer benefits like enhanced bioavailability, targeted delivery, improved stability, and reduced side effects. Innovative formulation strategies, including surface functionalization, particle size optimization, and use of biodegradable carriers, support controlled and sustained drug release. Additionally, production in non-aqueous media further enhances solubility and formulation efficiency. Despite these advancements, nano-formulations face challenges such as aggregation, manufacturing limitations, and regulatory compliance. Regulatory bodies like the FDA and EMA have established guidelines to ensure the safe development and application of nanomedicine. Looking ahead, nanotechnology play an important role in precision medicine, especially for treating cancer, neurological disorders, and infectious diseases. Moreover, its expanding applications in diagnostics and vaccine delivery underscore its importance in future of healthcare.
Keywords: Nanocarriers; Nanoformulations; Solubility enhancement; Therapeutic efficacy; nanotechnology; polymeric nanoparticles